Kajian Etnobotani dalam Pemanfaatan Tumbuhan Obat Tradisional di Kecamatan Pana Kabupaten Mamasa, Sulawesi Barat - Syamsiah, Syamsiah; Karim, Hilda; Arsal, Andi Faridah; Sondok, Sirumba (bionature, 2021)
Abstract. This study aims to: 1) determine the types of plants used as traditional medicine; (2) knowing the parts (organs) of plants used to treat diseases; (3) know how to process medicinal plants; and (4) knowing diseases that can be treated using medicinal plants in Pana District, Mamasa Regency, West Sulawesi. This research is a descriptive research with an exploratory nature. Data was collected through interviews, observation and identification. The results showed that from the 7 informants interviewed, 35 plant species from 22 families were obtained. Parts (organs) of plants that are generally used are one or all parts in the form of tubers, roots, stems, leaves and shoots. The processing of medicinal plants can be used directly, which is eaten without being processed first or processed by pounding, boiling, watering, grating, kneading, soaking, and or burning. Diseases treated are jaundice, typhoid, breast cancer, nerves, fever, ulcers, uterine cancer, brain cancer, kidney, burns, common wounds, gout, vaginal discharge, diarrhea, hemorrhoids, cholesterol, tuberculosis (TB), diabetes, rheumatism, headache, asthma, dengue fever, cough, smallpox, infection, speed up labor, remove spots on the body, neutralize toxins, and lower blood pressure.Keywords: medicinal plants, traditional medicine, pana district, mamasa regency, west sulawesi.